Design and Construction of an Electric Whip for the Implementation of Criminal Law in Aceh - Faujan, Faujan; Lastya, Hari Anna; Ikhsan, Muhammad (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
According to Qanun Jinayat, caning punishment in Aceh needs to be applied in a way that is both efficient and quantifiable. Designing an electric machine-based whipping device that controls the voltage (between 100 and 150 volts) according to the device's strength is the goal of the study. Using an experimental approach, this study displays the outcomes of 10 lashes at 100 volts for 10 seconds. It just takes 4.38 seconds at 150 volts. The punishments of khalwat (10–30 lashes), khamar (40–60 lashes), and zina (100 lashes) were used to test the system. The Aceh Jinayat law's concepts of justice and welfare are used to adjust the tension to the convict's circumstances. It is anticipated that this specially made whipping machine will be the most appropriate and compassionate way to administer caning punishment in Aceh. Therefore, this design provides a quantifiable, quick, and efficient method without disregarding the humanitarian element in Aceh's application of Islamic law.